Liquid-solid friction nanometer generator and preparation method thereof
By designing multiple groove structures and hydrophilic layers on the surface of liquid-solid friction nanogenerators, the problem of fog being difficult to condense into water droplets is solved, the current generation amount and energy collection efficiency are improved, and the application range of the equipment is expanded.
Patent Information
- Application Number
- CN202411447827.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
AI Technical Summary
When existing liquid-solid friction nanogenerators directly use mist as a droplet source, mist is difficult to condense into water droplets, resulting in insufficient current generation.
A liquid-solid friction nanogenerator is designed, with a surface covered with a deposited layer and a hydrophilic layer of multiple groove structures. The groove structure is used to form a hydrophobic effect. The hydrophilic layer is filled in the groove to aggregate and condense. Fog forms water droplets to generate electric current.
It effectively improves the current generation amount when mist condenses into water droplets and slides down on the surface of the generator, expands the application range of the equipment, and improves the energy harvesting efficiency.
Smart Images

Figure CN119210205A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of friction nanogenerators, and in particular to a liquid-solid friction nanogenerator and a preparation method thereof. Background Art
[0002] With the growing demand for energy and the intensification of environmental problems, finding a new and sustainable energy technology has become a global research focus. Triboelectric Nanogenerator (TENG) is a new type of power generation device. TENG uses the friction between two objects to generate charge transfer and convert mechanical energy into electrical energy. Liquid-Solid Triboelectric Nanogenerator (LS TENG) is a special energy collection form of TENG, which generates charge transfer by using the friction between liquid and solid materials.
[0003] Liquid-solid friction nanogenerators are based on the triboelectric effect and electrostatic induction effect, converting mechanical energy into electrical energy through the interaction between liquid and solid surface. Different frictions will result in different gains and losses of electrons. When the triboelectric layer material contacts the liquid and flows over the solid surface, electron transfer will occur between the electrons in the droplets, the triboelectric layer, and the electrodes. Taking polytetrafluoroethylene (PTFE) as the triboelectric layer as an example, when the water droplets are in continuous contact with PTFE, the electrons in the water droplets are attracted by PTFE to the contact surface with the water droplets. Due to the polarization phenomenon, the positive and negative charges in the PTFE layer will be gathered on the back contact surface of the water droplets and the contact surface with the water droplets respectively; and according to the principle of electrical neutrality, if the number of positive charges on the back contact surface of the PTFE layer with the water droplets is equal to the number of negative charges, the excess electrons will be transferred to the electrode (or the ground), thus generating current.
[0004] The liquid-solid friction nanogenerator in the related technology includes a dielectric layer and a conductive layer. The main function of the dielectric layer is to isolate the conductive layer from the liquid, forming a capacitor. The dielectric layer can enhance the charge separation effect during friction. The conductive layer is located under the dielectric layer. Its main function is to collect and export the charges generated in the dielectric layer during friction. When friction occurs, the charges in the dielectric layer will gather on the conductive layer to form an electric current. The dielectric layer is usually a hydrophobic material, such as polytetrafluoroethylene, and the conductive layer is made of copper platinum and other materials.
[0005] The liquid-solid friction nanogenerator in the related technology is mainly used to collect energy from water droplets in the ocean or rainy days. If the fog in the environment is used as the droplet source, it can not only improve the environmental adaptability of the liquid-solid friction nanogenerator, allowing the liquid-solid friction nanogenerator to work under a wider range of geographical and climatic conditions, but also the liquid-solid friction nanogenerator can be used for specific industrial application environmental monitoring.
[0006] However, the inventors found that the surface of the liquid-solid friction nanogenerator in the related art is a hydrophobic material. When mist is directly used as a droplet source, it is difficult for the mist to condense into water droplets on the surface of the liquid-solid friction nanogenerator. Usually, the mist is blown away by the airflow and can only generate a small current. Therefore, how to increase the current generated by the liquid-solid friction nanogenerator when mist is directly used as a droplet source has become a technical problem that needs to be solved urgently. Summary of the invention
[0007] The present invention discloses a liquid-solid friction nanogenerator and a preparation method thereof, in order to solve the technical problem in the related art that when mist is directly used as a droplet source in the liquid-solid friction nanogenerator, it is difficult for mist to condense into water droplets on the surface of the liquid-solid friction nanogenerator.
[0008] In order to solve the above problems, the present invention adopts the following technical solutions: A first aspect of the present invention provides a liquid-solid friction nanogenerator.
[0009] The liquid-solid friction nanogenerator of the present invention comprises a substrate, a deposition layer and a hydrophilic layer, wherein the deposition layer covers the substrate, a plurality of groove structures are formed on the surface of the deposition layer, the groove structures are arranged at intervals, the hydrophilic layer is made of a hydrophilic material, the hydrophilic layer is filled in the groove structure, and the surface of the hydrophilic layer is higher than the surface of the groove structure, or the surface of the hydrophilic layer is flush with the surface of the groove structure.
[0010] According to an optional embodiment, the inner diameter of the groove structure is 150 μm to 500 μm.
[0011] According to an optional embodiment, the distance between the centers of two adjacent groove structure surfaces is 250 μm to 550 μm.
[0012] The second aspect of the present invention provides a method for preparing a liquid-solid friction nanogenerator.
[0013] The method for preparing the liquid-solid friction nanogenerator described in any technical solution of the present invention comprises the following steps: S100: preparing a substrate, and placing the substrate in a plasma cleaning machine for cleaning; S200: mixing the discrete phase with the continuous phase to form a mixed fluid in which the continuous phase envelops the discrete phase, and spraying the mixed fluid on the surface of the substrate, whereby the mixed fluid is deposited on the substrate to form a deposited layer; S300: soaking the substrate obtained in step S200 in a solvent to remove the discrete phase and form a plurality of groove structures on the surface of the deposited layer; S400: placing the substrate obtained in step S300 in a cross-linking liquid for reaction, thereby modifying the deposited layer and making the deposited layer insoluble in water; S500: Immersing the substrate obtained in step S400 in a hydrophilic material, and filling the groove structure with the hydrophilic material under vacuum conditions.
[0014] According to an optional embodiment, in step S200, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 15~30 cSt, and the weight of the polysiloxane is 1~5% of the weight of the silicone oil; the continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30000~70000, the hydrolysis rate of the polyvinyl alcohol is 87~89%, and the weight fraction of the polyvinyl alcohol is 5~10%.
[0015] According to an optional embodiment, in step S200, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 20 cSt and the weight of the polysiloxane is 2% of the weight of the silicone oil; the continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30,000-70,000, the hydrolysis rate of the polyvinyl alcohol is 87-89%, and the weight fraction of the polyvinyl alcohol is 7%.
[0016] According to an optional implementation, in step S200, when the discrete phase and the continuous phase are mixed, the flow ratio of the discrete phase to the continuous phase is controlled to be 1-6:12-20.
[0017] According to an optional implementation, in step S200, when the discrete phase is mixed with the continuous phase, the distance between the first quartz cone tube and the second quartz cone tube is controlled to be 0.1 mm to 7 mm.
[0018] According to an optional embodiment, the cross-linking liquid used in step S400 is: a mixture of 10% by volume glutaraldehyde and 90% by volume acetone, the pH of the mixture is adjusted to 2-3 with HCl, and the temperature when the substrate obtained in step S300 reacts with the cross-linking liquid is 40°C, and the reaction time is 24 hours.
[0019] According to an optional embodiment, in step S500, after the substrate obtained in step S400 is immersed in a hydrophilic material, the substrate is controlled to be under a pressure of 60-80 KPa and a room temperature, and the immersion time of the substrate is greater than or equal to 1 hour.
[0020] The technical solution adopted by the present invention can achieve the following beneficial effects: In the first aspect, the liquid-solid friction nanogenerator of the present invention comprises a substrate, a deposition layer and a hydrophilic layer, wherein the deposition layer is covered on the substrate, and a plurality of groove structures are formed on the surface of the deposition layer, and the groove structures are arranged at intervals, and the groove structures on the deposition layer make the deposition layer hydrophobic; the hydrophilic layer is filled in the groove structure, and the surface of the hydrophilic layer is higher than the surface of the groove structure, or the surface of the hydrophilic layer is flush with the surface of the groove structure, that is, the surface of the liquid-solid friction nanogenerator is a hydrophilic layer. When the mist passes through the surface of the liquid-solid friction nanogenerator, under the action of the hydrophilic layer, the mist gathers on the surface of the liquid-solid friction nanogenerator to form droplets, and the droplets can penetrate the hydrophilic layer and enter the inside of the hydrophilic layer, forming a form in which the hydrophilic layer wraps the droplets, and when the droplets condense to a certain extent, they form water droplets, and under the hydrophobic action of the deposition layer, the water droplets can slide off the surface of the liquid-solid friction nanogenerator and generate current. The liquid-solid friction nanogenerator of the present invention can use the mist in the environment as a liquid source, which expands the application range of the liquid-solid friction nanogenerator.
[0021] It can be seen that when the mist passes through the surface of the liquid-solid friction nanogenerator of the present invention, it can condense into water droplets on its surface and fall off. Compared with the current generated by the falling mist droplets, the falling water droplets of the present invention can generate a larger current. That is, the liquid-solid friction nanogenerator of the present invention solves the technical problem that when the liquid-solid friction nanogenerator in the related art directly uses mist as the droplet source, the mist is difficult to condense into water droplets on the surface of the liquid-solid friction nanogenerator.
[0022] Secondly, the groove structure of the liquid-solid friction nanogenerator of the present invention can not only make the deposited layer hydrophobic, but also provide a holding space for the hydrophilic layer to accommodate the hydrophilic reagent. Compared with the structure in which the hydrophilic reagent is directly covered on the plane, the groove structure of the present invention can increase the thickness of the hydrophilic layer. During the nucleation and condensation process of droplets, the increase in the thickness of the hydrophilic layer can accelerate the condensation rate of the droplets. The accelerated condensation rate of the droplets is beneficial to improving the energy collection efficiency of the liquid-solid friction nanogenerator. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 is a schematic diagram of spraying a mixed fluid onto a substrate in an embodiment of the present application; Figure 2 is a schematic diagram of the mixed fluid after being deposited on a substrate in an embodiment of the present application; Figure 3This is a schematic diagram of an embodiment of the present application after removing the discrete phase; Figure 4 is a schematic diagram of a liquid-solid friction nanogenerator according to an embodiment of the present application; Figure 5 is a schematic diagram of an experimental device for preparing a liquid-solid friction nanogenerator according to an embodiment of the present application; Figure 6 is a schematic diagram of the cooperation between the first quartz cone tube, the second quartz cone tube and the capillary tube; Figure 7 is a schematic diagram of an inverted cone press plug according to an embodiment of the present application; Figure 8 is a schematic diagram of an inverted cone pressure ring according to an embodiment of the present application; Fig. 9 It is a schematic diagram of a water droplet entering the hydrophilic layer and being wrapped by the hydrophilic layer.
[0025] In the figure: 1, high-power light source; 2, high-speed camera; 3, computer; 4, first injection pump; 5, second injection pump; 6, three-way connector; 7, first conduit; 8, second conduit; 9, capillary; 10, straight connector; 11, third conduit; 12, first quartz cone tube; 13, second quartz cone tube; 14, inverted cone plug; 15, inverted cone pressure ring; 110, substrate; 120, deposition layer; 121, groove structure; 130, hydrophilic layer. DETAILED DESCRIPTION
[0026] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0027] The terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.
[0028] The following is combined with Figures 1 to 9, the liquid-solid friction nanogenerator and its preparation method provided in the embodiments of the present application are described in detail through specific embodiments and their application scenarios.
[0029] A first aspect of this embodiment provides a liquid-solid friction nanogenerator.
[0030] The liquid-solid friction nanogenerator of this embodiment includes a substrate 110, such as Figure 4 As shown. Exemplarily, the substrate 110 is made of phosphor bronze, and the size is determined by the size of the planned surface. The phosphor bronze material is selected as the substrate 110, so that the substrate 110 has good conductivity and corrosion resistance. Not limited to this, the substrate 110 can also be made of other conductive materials.
[0031] In some embodiments, the liquid-solid friction nanogenerator includes a substrate 110 and a deposition layer 120, such as Figure 4 Preferably, the deposition layer 120 covers the substrate 110, and a plurality of groove structures 121 are formed on the surface of the deposition layer 120, and the groove structures 121 are arranged at intervals, such as Figure 4 As shown. Exemplarily, the groove structure 121 is a circular, square, elliptical structure, etc. This structure of the deposition layer 120 enables the deposition layer 120 to have a structural hydrophobic function.
[0032] Exemplarily, the deposition layer 120 is made of polyvinyl alcohol (PVA) material. The deposition layer 120 is made of polyvinyl alcohol (PVA) material, so that the deposition layer 120 is flexible and can be peeled off from the substrate 110, so that the deposition layer 120 of the present application can be combined with other conductive materials and is suitable for various scenarios.
[0033] In some embodiments, the liquid-solid friction nanogenerator includes a substrate 110 and a hydrophilic layer 130, such as Figure 4 Preferably, the hydrophilic layer 130 is made of a hydrophilic material, and the hydrophilic layer 130 is filled in the groove structure 121, as shown. Figure 4 More preferably, the surface of the hydrophilic layer 130 is higher than the surface of the groove structure 121 , or the surface of the hydrophilic layer 130 is flush with the surface of the groove structure 121 .
[0034] For example, the hydrophilic layer 130 is made of trimethoxysilane, but is not limited thereto, and the hydrophilic layer 130 may also be made of other hydrophilic materials.
[0035] In the first aspect, the liquid-solid friction nanogenerator of the present embodiment includes a substrate 110, a deposition layer 120 and a hydrophilic layer 130. The deposition layer 120 covers the substrate 110. A plurality of groove structures 121 are formed on the surface of the deposition layer 120. The groove structures 121 are arranged at intervals. The groove structures 121 on the deposition layer 120 make the deposition layer 120 hydrophobic. The hydrophilic layer 130 is filled in the groove structure 121, and the surface of the hydrophilic layer 130 is higher than the surface of the groove structure 121, or the surface of the hydrophilic layer 130 is flush with the surface of the groove structure 121, that is, the surface of the liquid-solid friction nanogenerator is the hydrophilic layer 130. When the mist passes through the surface of the liquid-solid friction nanogenerator, under the action of the hydrophilic layer 130, the mist gathers on the surface of the liquid-solid friction nanogenerator to form droplets. The droplets can penetrate the hydrophilic layer 130 and enter the interior of the hydrophilic layer 130, forming a form in which the hydrophilic layer 130 wraps the droplets (such as Fig. 9 As shown in FIG. 1 ), when the mist droplets condense to a certain extent to form water droplets, the water droplets can slide down from the surface of the liquid-solid friction nanogenerator under the hydrophobic effect of the deposition layer 120 and generate current. Therefore, the liquid-solid friction nanogenerator of this embodiment can use the mist in the environment as a liquid source, which expands the application range of the liquid-solid friction nanogenerator.
[0036] It can be seen that when the mist passes through the surface of the liquid-solid friction nanogenerator of this embodiment, it can condense into water droplets on its surface and fall off. Compared with the current generated by the falling mist droplets, the falling water droplets of this embodiment can generate a larger current. That is, the liquid-solid friction nanogenerator of this embodiment solves the technical problem that when the liquid-solid friction nanogenerator in the related art directly uses mist as the droplet source, the mist is difficult to condense into water droplets on the surface of the liquid-solid friction nanogenerator.
[0037] Secondly, in the liquid-solid friction nanogenerator of this embodiment, the groove structure 121 can not only make the deposition layer 120 hydrophobic, but also provide a holding space for the hydrophilic layer 130 for accommodating hydrophilic reagents. Compared with the structure in which the hydrophilic reagents are directly covered on the plane, the groove structure 121 of this embodiment can increase the thickness of the hydrophilic layer 130. During the nucleation and condensation process of droplets, the increase in the thickness of the hydrophilic layer 130 can accelerate the condensation rate of the droplets. The accelerated condensation rate of the droplets is beneficial to improving the energy collection efficiency of the liquid-solid friction nanogenerator.
[0038] In some embodiments, the inner diameter of the groove structure 121 is 150 μm to 500 μm. For example, the inner diameter of the groove structure 121 is 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, or 500 μm.
[0039] The liquid-solid friction nanogenerator of this embodiment helps to maintain a faster condensation rate of the droplets by controlling the inner diameter of the groove structure 121 to 150 μm to 500 μm, thereby helping to maintain a higher energy collection efficiency of the liquid-solid friction nanogenerator. If the inner diameter of the groove structure 121 is too large, the bottom size of the groove structure 121 is small, and when the deposition layer 120 is dried, the hydrophilic reagent is prone to leak from the bottom of the groove structure 121.
[0040] In some embodiments, the distance between the centers of the surfaces of two adjacent groove structures 121 is 250 μm to 550 μm. Exemplarily, the distance between the centers of the surfaces of two adjacent groove structures 121 is 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm. Exemplarily, when the groove structure 121 is circular, the size of the opening of the groove structure 121 is smaller than the inner diameter of the groove structure 121, or the size of the opening of the groove structure 121 is larger than the inner diameter of the groove structure 121.
[0041] The number of the groove structures 121 may be determined based on the specific size of the deposition layer 120 .
[0042] The liquid-solid friction nanogenerator of this embodiment controls the distance between the centers of the surfaces of two adjacent groove structures 121 to be 250 μm to 550 μm, which is conducive to maintaining good hydrophobicity of the deposition layer 120. If the distance between the centers of the surfaces of two adjacent groove structures 121 is too large, not only the hydrophobicity of the deposition layer 120 is poor, but also the deposition layer 120 can accept less hydrophilic reagents.
[0043] A second aspect of this embodiment provides an experimental device for preparing a liquid-solid friction nanogenerator.
[0044] like Figure 5 As shown, the experimental device for preparing the liquid-solid friction nanogenerator includes a high-power light source 1, a high-speed camera 2, and a computer 3. The high-power light source 1 is used to supplement the light for the high-speed camera 2. The high-speed camera 2 is used to capture the dynamic behavior of the discrete phase and the continuous phase in the tube at different propulsion speeds of the microinjection pump. The computer 3 is used to record the image information captured by the high-speed camera 2.
[0045] like Figure 5As shown, the experimental device for preparing the liquid-solid friction nanogenerator also includes a first injection pump 4 and a second injection pump 5. The first injection pump 4 includes a first propulsion unit and a first liquid storage unit, the first liquid storage unit stores a continuous phase fluid, and the first propulsion unit is used to push out the continuous phase fluid in the first liquid storage unit. The second injection pump 5 includes a second propulsion unit and a second liquid storage unit, the second liquid storage unit stores a discrete phase fluid, and the second propulsion unit is used to push out the discrete phase fluid in the second liquid storage unit. Exemplarily, the first propulsion unit and the second propulsion unit include a motor and a screw, and the screw and the motor work together to push the continuous phase fluid and the discrete phase fluid into the tube to form a continuous phase enveloping a discrete phase mixed fluid.
[0046] like Figure 5 As shown, the experimental device for preparing the liquid-solid friction nanogenerator also includes a three-way joint 6, a first conduit 7, a second conduit 8, a capillary 9, a straight joint 10 and a third conduit 11. The two ends of the first conduit 7 are respectively connected to the first injection pump 4 and the first interface of the three-way joint 6, the two ends of the second conduit 8 are respectively connected to the second injection pump 5 and the second interface of the three-way joint 6, the two ends of the capillary 9 are respectively connected to the third interface of the three-way joint 6 and one end of the straight joint 10, and the third conduit 11 is connected to the other end of the straight joint 10. The substrate 110 is placed at the outlet of the third conduit 11.
[0047] Exemplarily, the outer diameter of the three-way connector 6 is 9 mm.
[0048] Exemplarily, the straight connector 10 has a diameter of 9 mm and a length of 22.5 mm.
[0049] Exemplarily, the inner diameters of the first conduit 7, the second conduit 8 and the third conduit 11 are 1 mm and the outer diameters are 2.4 mm. The first conduit 7 is used to transport continuous phase fluid, the second conduit 8 is used to transport dispersed phase fluid, and the third conduit 11 is used to transport a mixed fluid of continuous phase and dispersed phase.
[0050] Exemplarily, the capillary tube 9 is a square capillary tube, the outer wall and the inner hole of the capillary tube 9 are both square, the side length of the outer hole is 1.4 mm, the side length of the inner hole is 1.1 mm, and the tube length is 100 mm.
[0051] like Figure 6 As shown, the experimental device for preparing the liquid-solid friction nanogenerator also includes a first quartz cone tube 12 and a second quartz cone tube 13, and the first quartz cone tube 12 and the second quartz cone tube 13 are arranged in the capillary 9. The first quartz cone tube 12 and the second quartz cone tube 13 are arranged at intervals, and the tube mouth diameter of the first quartz cone tube 12 is larger than the tube mouth diameter of the second quartz cone tube 13. There is a gap between the first quartz cone tube 12 and the second quartz cone tube 13 and the capillary 9, which can facilitate the flow of the continuous phase fluid.
[0052] Exemplarily, the first quartz cone tube 12 has an inner diameter of 0.5 mm, an outer diameter of 1 mm, a cone tube mouth diameter of 0.2 mm, and a tube length of 60 mm.
[0053] Exemplarily, the second quartz cone tube 13 has an inner diameter of 0.5 mm, an outer diameter of 1 mm, a cone tube mouth diameter of 0.15 mm, and a tube length of 60 mm.
[0054] like Figure 7 and Figure 8 As shown, the experimental device for preparing the liquid-solid friction nanogenerator also includes an inverted cone pressure plug 14 and an inverted cone pressure ring 15. The inverted cone pressure plug 14 is used to fix the first conduit 7, the second conduit 8, the capillary 9 and the third conduit 11 in the three-way joint 6 or the straight joint 10. Exemplarily, the inner diameter of the thinnest part of the inverted cone pressure plug 14 is 2.5 mm. The inverted cone pressure plug 14 is connected to the three-way joint 6 or the straight joint 10 by threads. The inverted cone pressure ring 15 is clamped on one end of the inverted cone pressure plug 14 with a threaded structure. Through the joint action of the inverted cone pressure ring 15 and the inverted cone pressure plug 14, the stability of the installation of the first conduit 7, the second conduit 8, the capillary 9 and the third conduit 11 can be enhanced to prevent the first conduit 7, the second conduit 8, the capillary 9 and the third conduit 11 from moving.
[0055] A third aspect of this embodiment provides a method for preparing a liquid-solid friction nanogenerator.
[0056] The preparation method of the liquid-solid friction nanogenerator of this embodiment is completed based on an experimental device for preparing the liquid-solid friction nanogenerator according to any one of the technical solutions of this embodiment.
[0057] The preparation method of the liquid-solid friction nanogenerator of this embodiment is used to prepare the liquid-solid friction nanogenerator of any technical solution of this embodiment.
[0058] The preparation method of the liquid-solid friction nanogenerator of this embodiment comprises the following steps: S100: preparing a substrate 110, and placing the substrate 110 in a plasma cleaning machine for cleaning.
[0059] Exemplarily, the substrate 110 is a phosphor bronze substrate, and the substrate 110 is placed in a plasma cleaning machine for cleaning for more than 30 minutes, thereby improving the hydrophilicity of the surface of the substrate 110 without changing the surface structure of the substrate 110. The improved hydrophilicity of the surface of the substrate 110 can make the material of the deposition layer 120 diffuse better on the surface of the substrate 110, and at the same time can reduce the thickness of the deposition layer 120, so that the deposition layer 120 can maintain good flexibility and flatness.
[0060] S200: Mixing the discrete phase with the continuous phase to form a mixed fluid in which the continuous phase envelops the discrete phase, and spraying the mixed fluid on the surface of the substrate 110. The mixed fluid is deposited on the substrate 110 to form a deposition layer 120, such as Figure 1 and Figure 2 shown.
[0061] In some embodiments, after the mixed fluid is deposited on the substrate 110 , it is dried by natural convection at room temperature to form the deposition layer 120 .
[0062] In some embodiments, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 15~30 cSt, and the weight of the polysiloxane is 1~5% of the weight of the silicone oil; the continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30000~70000, the hydrolysis rate of the polyvinyl alcohol is 87~89%, and the weight fraction of the polyvinyl alcohol is 5~10%.
[0063] In some embodiments, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 20 cSt and the weight of the polysiloxane is 2% of the weight of the silicone oil; the continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30,000-70,000, the hydrolysis rate of the polyvinyl alcohol is 87-89%, and the weight fraction of the polyvinyl alcohol is 7%.
[0064] Without being limited to this, other fluids may also be used as the discrete phase and the continuous phase.
[0065] The discrete phase of this embodiment includes silicone oil and polysiloxane, and the continuous phase includes polyvinyl alcohol and ultrapure water. When the discrete phase is mixed with the continuous phase, the silicone oil and polyvinyl alcohol can form a stable emulsion. The polysiloxane in the discrete phase can be used as a surfactant to improve the compatibility of silicone oil and polyvinyl alcohol and reduce phase separation. On the other hand, polyvinyl alcohol as the main component of the deposition layer 120 makes the deposition layer 120 flexible and can be peeled off from the substrate 110, so that the deposition layer 120 of the present application can be combined with other conductive materials and is suitable for a variety of scenarios.
[0066] Reference Figure 5 and Figure 6 As shown, the flow paths of the discrete phase and the continuous phase of this embodiment are as follows: The continuous phase pushed out by the first injection pump 4 enters the first conduit 7 and flows into the three-way joint 6 along the first conduit 7, and then flows in the gap between the first quartz cone tube 12 and the capillary 9. Since the first quartz cone tube 12 and the second quartz cone tube 13 are arranged at intervals, the continuous phase can flow to the gap between the first quartz cone tube 12 and the second quartz cone tube 13.
[0067] The dispersed phase pushed out by the second injection pump 5 enters the second conduit 8, and flows into the three-way joint 6 along with the second conduit 8, and then the dispersed phase enters the first quartz cone tube 12. Since the first quartz cone tube 12 and the second quartz cone tube 13 are arranged at intervals, the dispersed phase flowing out of the first quartz cone tube 12 can be mixed with the continuous phase at the gap to form a mixed fluid in which the continuous phase envelops the dispersed phase. Subsequently, the mixed fluid enters the second quartz cone tube 13, and is sprayed onto the surface of the substrate 110 through the straight joint 10 and the third conduit 11.
[0068] In some embodiments, when the dispersed phase is mixed with the continuous phase, the flow rate ratio of the dispersed phase to the continuous phase is controlled to be 1-6:12-20. Exemplarily, the flow rate of the dispersed phase is 0.5-3 μL / min, and the flow rate of the continuous phase is 6-10 μL / min. Exemplarily, the flow rate of the dispersed phase is 0.5 μL / min, and the flow rate of the continuous phase is 6 μL / min.
[0069] In some embodiments, when the discrete phase is mixed with the continuous phase, the spacing between the first quartz cone tube 12 and the second quartz cone tube 13 is controlled to be 0.1 mm to 7 mm. Exemplarily, the spacing between the first quartz cone tube 12 and the second quartz cone tube 13 is 0.1 mm, 0.3 mm, 0.5 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, and 7 mm.
[0070] In this step, by controlling the flow ratio of the discrete phase to the continuous phase and / or adjusting the distance between the first quartz cone tube 12 and the second quartz cone tube 13, the size of the droplets generated by the discrete phase can be controlled, thereby adjusting the size of the groove structure 121. This control method is easy to operate and has high reliability.
[0071] In this embodiment, the flow ratio of the discrete phase to the continuous phase is controlled to be 1-6:12-20, and / or the spacing between the first quartz cone tube 12 and the second quartz cone tube 13 is controlled to be 0.1 mm-7 mm, so that the inner diameter of the prepared groove structure 121 is 150 μm-500 μm, so as to ensure that the liquid-solid friction nanogenerator has a higher energy conversion efficiency.
[0072] This embodiment utilizes the flow rate difference between the discrete phase and the continuous phase, and the continuous phase generates a shear force on the discrete phase, so that the originally continuous discrete phase is sheared into small bubbles of equal size at the cone mouth of the first quartz cone tube 12, thereby forming a mixed fluid in which the continuous phase envelops the discrete phase. Specifically, the faster the flow rate of the continuous phase, the smaller the discrete phase bubbles and the fewer the number. By adjusting the flow ratio of the discrete phase to the continuous phase and / or adjusting the spacing between the first quartz cone tube 12 and the second quartz cone tube 13, the size and number of the small bubbles can be changed, thereby achieving the effect of controlling the size of the groove structure 121.
[0073] S300: Soak the substrate 110 obtained in step S200 in a solvent to remove the discrete phase and form a plurality of groove structures 121 on the surface of the deposition layer 120, such as Figure 3 shown.
[0074] In some embodiments, the solvent used to soak the substrate 110 is n-hexane, and the soaking time is more than 2 hours. The substrate 110 obtained in step S200 is soaked in n-hexane to remove oil stains on the substrate 110, that is, to remove silicone oil, so that a plurality of groove structures 121 are formed on the surface of the deposition layer 120.
[0075] S400: placing the substrate 110 obtained in step S300 in a cross-linking solution for reaction, thereby modifying the deposited layer 120 and making the deposited layer 120 insoluble in water.
[0076] In some embodiments, the cross-linking liquid is a mixture of 10% by volume glutaraldehyde and 90% by volume acetone, and the pH of the mixture is adjusted to 2-3 with HCl.
[0077] In some embodiments, the substrate 110 obtained in step S300 reacts with the cross-linking liquid at a temperature of 40° C. and a reaction time of 24 hours.
[0078] The substrate 110 obtained in step S300 is placed in a cross-linking liquid for reaction, and is taken out and rinsed with ultrapure water and naturally air-dried. The deposition layer 120 can be made insoluble in water through modification, thereby preventing droplets from affecting the deposition layer 120 during the subsequent use of the liquid-solid friction nanogenerator.
[0079] S500: Soak the substrate 110 obtained in step S400 in a hydrophilic material, and fill the groove structure 121 with the hydrophilic material under vacuum conditions, such as Figure 4 shown.
[0080] In some embodiments, the substrate 110 obtained in step S400 is rinsed with ultrapure water and dried naturally, and then immersed in a hydrophilic material and placed in a vacuum drying oven. The pressure in the vacuum drying oven is controlled to be 60-80Kpa, the temperature is room temperature, and the immersion time of the substrate 110 is greater than or equal to 1 hour, so that the hydrophilic material can fill the groove structure 121. Exemplarily, the hydrophilic material is trimethoxysilane.
[0081] In this embodiment, the pressure in the vacuum drying box is controlled to be 60-80 KPa, which is not only conducive to maintaining the integrity of the groove structure 121, but also allows the hydrophilic material to fill the groove structure 121. Specifically, if the pressure is too small, such as under a complete vacuum condition, the groove structure 121 will be destroyed; if the pressure is too large, it is difficult for the hydrophilic material to fill the groove structure 121.
[0082] In some embodiments, the circuit is led out from the substrate 110 by wires.
[0083] Through the above steps, a liquid-solid friction nanogenerator of any technical solution in this embodiment can be prepared. The surface of the liquid-solid friction nanogenerator has good hydrophilicity, which can collect moisture in the air and condense into small water droplets, which then slide off the surface to generate charge transfer.
[0084] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0085] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A liquid-solid friction nanogenerator, characterized in that: The invention comprises a substrate (110), a deposition layer (120) and a hydrophilic layer (130), wherein the deposition layer (120) covers the substrate (110), a plurality of groove structures (121) are formed on the surface of the deposition layer (120), the groove structures (121) are arranged at intervals, the hydrophilic layer (130) is made of a hydrophilic material, the hydrophilic layer (130) is filled in the groove structures (121), and the surface of the hydrophilic layer (130) is higher than the surface of the groove structures (121), or the surface of the hydrophilic layer (130) is flush with the surface of the groove structures (121).
2. The liquid-solid friction nanogenerator according to claim 1, characterized in that: The inner diameter of the groove structure (121) is 150 μm to 500 μm.
3. The liquid-solid friction nanogenerator according to claim 1, characterized in that: The distance between the surface centers of two adjacent groove structures (121) is 250 μm to 550 μm.
4. The method for preparing a liquid-solid friction nanogenerator according to any one of claims 1 to 3, characterized in that: The steps include: S100: preparing a substrate (110), and placing the substrate (110) in a plasma cleaning machine for cleaning; S200: mixing the discrete phase and the continuous phase to form a mixed fluid in which the continuous phase envelops the discrete phase, and spraying the mixed fluid onto the surface of the substrate (110); the mixed fluid is deposited on the substrate (110) to form a deposited layer (120); S300: soaking the substrate (110) obtained in step S200 in a solvent to remove the discrete phase and form a plurality of groove structures (121) on the surface of the deposited layer (120); S400: placing the substrate (110) obtained in step S300 in a cross-linking liquid for reaction, thereby modifying the deposited layer (120) and making the deposited layer (120) insoluble in water; S500: Immerse the substrate (110) obtained in step S400 in a hydrophilic material, and fill the groove structure (121) with the hydrophilic material under vacuum conditions.
5. The method for preparing a liquid-solid friction nanogenerator according to claim 4, characterized in that: In step S200, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 15-30 cSt, and the weight of the polysiloxane is 1-5% of the weight of the silicone oil; The continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30000-70000, the hydrolysis rate of the polyvinyl alcohol is 87-89%, and the weight fraction of the polyvinyl alcohol is 5-10%.
6. The method for preparing a liquid-solid friction nanogenerator according to claim 5, characterized in that: In step S200, the discrete phase includes silicone oil and polysiloxane, wherein the viscosity of the silicone oil is 20 cSt, and the weight of the polysiloxane is 2% of the weight of the silicone oil; The continuous phase includes polyvinyl alcohol and ultrapure water, wherein the molecular weight of the polyvinyl alcohol is 30000-70000, the hydrolysis rate of the polyvinyl alcohol is 87-89%, and the weight fraction of the polyvinyl alcohol is 7%.
7. The method for preparing a liquid-solid friction nanogenerator according to claim 4, characterized in that: In step S200, when the dispersed phase and the continuous phase are mixed, the flow rate ratio of the dispersed phase to the continuous phase is controlled to be 1-6:12-20.
8. The method for preparing a liquid-solid friction nanogenerator according to claim 4, characterized in that: In step S200, when the discrete phase and the continuous phase are mixed, the distance between the first quartz cone tube (12) and the second quartz cone tube (13) is controlled to be 0.1 mm to 7 mm.
9. The method for preparing a liquid-solid friction nanogenerator according to claim 4, characterized in that: The cross-linking liquid used in step S400 is a mixture of 10% by volume glutaraldehyde and 90% by volume acetone, wherein the pH of the mixture is adjusted to 2-3 using HCl, and the substrate (110) obtained in step S300 reacts with the cross-linking liquid at a temperature of 40° C. for a reaction time of 24 h.
10. The method for preparing a liquid-solid friction nanogenerator according to claim 4, characterized in that: In step S500, after the substrate (110) obtained in step S400 is immersed in a hydrophilic material, the substrate (110) is controlled to be under conditions of a pressure of 60-80 KPa and a temperature of room temperature, and the immersion time of the substrate (110) is greater than or equal to 1 hour.